An integrated family approach in the practice of adult and child mental health care - Stolper, Hanna; van Doesum, Karin; Steketee, Majone (Frontiers in Psychiatry, 2024)
This paper describes the practice of an integrated family approach to treatment in mental health care in which the focus is on the whole family and treatment is carried out by professionals of adult and child mental health services together. It is presented as an example of a best practice in finding a way to overcome barriers in implementing an integrated family approach in treatment for the benefit of families with a variety of interrelated problems. Even though there is a lot of knowledge about the importance of a family approach in mental health care with specific attention to the patients’ parental role, the children, family relationships, and the social economic context, this is worldwide rarely implemented in the practice of mental health care. Barriers to keep the whole family in mind are identified on different levels: organizational policy, interagency collaboration, professionals, and patients themselves. As a solution, a model of an integrated family approach in mental health care is presented: how it is defined; which domains in the family are targeted; which key elements it contains; what the treatment consists of; and which procedures are followed in practice. A case illustrates how this approach might work in practice.